Ab initio description of the thermoelectric properties of heterostructures in the diffusive limit of transport - Hinsche, Nicki F.; Rittweger, Florian; Hoelzer, Martin; Zahn, Peter; Ernst, Arthur; Mertig, Ingrid; et al. (physica status solidi (a), 2016)
The scope of this review is to present the recent progress in the understanding of the microscopic origin of thermoelectric transport in semiconducting heterostructures and to identify and elucidate mechanisms which could lead to enhanced thermoelectric conversion efficiency. Based on first-principles calculations a consistent and convenient method is presented to fully describe the thermoelectric properties in the diffusive limit of transport for bulk systems and their associated heterostructures. While fundamentals of the functionality of phonon-blocking and electron-transmitting superlattices could be unveiled, we provide also distinct analysis and ideas for thermoelectric enhancement for two archetypical thermoelectric heterostructures based on Bi2Te3/Sb2Te3 and Si/Ge. A focus was on the influence of bulk and interfacial strain, varying charge carrier concentration, temperature, and superlattice periods on the thermoelectric transport properties. Transmission electron micrograph of a 10 Å/50 Å Bi2Te3/Sb2Te3 superlattice. Red and green areas highlight the layered structure. For optimal cross-plane transport (⊥) phonons (p) are expected to be scattered at the interfaces, while electrons (e-) transmit without losses. The microscopic origin of thermoelectric transport in semiconducting heterostructures shows up to be a promising tool to optimize the thermoelectric conversion efficiency. A consistent and convenient first-principles method is presented to fully describe the thermoelectric properties in the diffusive limit of transport for bulk systems and their associated heterostructures.
CRIS-Team Scopus Importer:2023-03-20
Keywords: ab initio calculations; chalcogenides; Charge carrier transport; heterostructures; silicon; thermoelectric properties